SOSIALISASI DAN PENYULUHAN HUKUM BAHAYA NARKOBA DENGAN TEMA “MEWUJUDKAN GENERASI MUDA ANTI NARKOBA” DI SMA NEGERI 1 PADARINCANG - Ratulangi, Ambo Rasyid; Agustiawan, M. Nassir; sae, Eli Apud; Muid, Abdul; Saputri, Cindi; Azzahra, Anneira; Sauzan, Zahra; Nada, Zanuba Qotrun; Nursinta; Natalia, Cristin; Febriyanti, Yeni; Julfadhli, Ardhi; Azzahra, Gladisya Audita; Sartika; Azhar, Intan Nabila; Yunengsih, Yuyun; Setyawan, Ferdy (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Socialization and legal counseling activities with the theme "Realizing a Young Generation Against Drugs" were held at SMA Negeri 1 Padarincang. This activity aims to provide students with an understanding of the dangers of drugs and their negative impact on personal and community life. Through this socialization, it is hoped that students can be more familiar with the laws related to drugs, and increase their awareness of the importance of staying away from drug use. This activity also aims to shape students' attitudes and behaviors in order to become a resilient, responsible, and committed young generation to live a healthy life without drugs. Thus, it is hoped that this socialization can contribute to creating a drug-free school environment and preparing a young generation with integrity and legal awareness.